Green Islamic Finance: Model Pembiayaan Syariah Berbasis Keberlanjutan untuk Mendukung Ekonomi Hijau di Indonesia - Azuwardi (Sujud: Jurnal Agama, Sosial dan Budaya, 2026)
The development of a green economy is a priority for Indonesia in addressing climate change and promoting sustainable development. Islamic finance can play a significant role through Green Islamic Finance, which integrates Sharia principles with sustainability values. This study examines the concept, policy framework, and potential Sharia-compliant financing models to support the green economic transition. Using a qualitative descriptive method, this research analyzes literature, regulations, and institutional reports. The findings indicate strong potential for instruments such as green sukuk, productive waqf, renewable-energy musyarakah, and qard hasan for green MSMEs. Optimization requires improved literacy, product innovation, policy support, and multi-stakeholder collaboration. The proposed model integrates Sharia principles, digital technology, and sustainability standards. These findings contribute to strengthening Green Islamic Finance and supporting national sustainable development goals.